Enhancement of acellular biomineralization, dental pulp stem cell migration, and differentiation by hybrid fibrin gelatin scaffolds. Issue 3 (March 2023) - Li, Kao; O'Dwyer, Rita; Yang, Fan; Cymerman, Jerome; Li, Juyi; Feldman, Jake D.; Simon, Marcia; Rafailovich, Miriam
Abstract: Objective: The current in vitro study aims to evaluate cross-linked hydrogels with and without the addition of fibrin that could potentially be used in endodontic regeneration as a scaffold material. Methods: Synthesis of gelatin/fibrin scaffold, and performing nanoscale characterization using cryo-electron microscopy, dynamic rheology, and XRF for structure property relations; plating dental pulp stem cells and determining mineralization, migration, and differentiation using rt-PCR, XRF, and Raman spectroscopy. Results: Cryo electron imaging shows gelatin and fibrin, when gelled separately to form classical rectangular cross-linked networks, where the modulus scales inversely with the cube root of the mesh size. When gelled together, a network with a fundamentally different structure is formed, which has higher ductility and when placed as a scaffold in osteogenic media, produces twice the mineral content. Immunofluorescence, RT-PCR and Rahman Spectroscopy indicate that the hybrid gel enhances cell migration, induces odontogenic differentiation of dental pulp stem cells, and promotes formation of dentin. Significance: The mechanical properties of the hybrid gel scaffold enhance in-migration of stem cells and subsequent differentiation, which are critical for regenerative procedures. Under acellular conditions, placement of the hybrid gel enhances biomineralization, which would strengthen the root if used as a scaffold for endodontic regeneration. Our in vitro findings are consistent with previous in vivo studies which show improved mineralization when bleeding is induced into the canal, given that fibrin is a primary component in blood clotting. Therefore, insertion of the hybrid gelatin-fibrin scaffold could enable more reproducible and consistent outcomes if used for regenerative endodontic treatment (RET). Graphical Abstract: ga1 Highlights: When gelled together, gelatin and fibrin form uniform yet different micro-network. Addition of fibrin into gelatin could enhance acellular biomineralization. When DPSCs are present, enhanced migration, odontogenetic differentiation are obtained by fibrin.